Characteristics and Fertilizer Effects of Soil‐Like Materials from Landfill Mining. Issue 6 (5th February 2015) - Zhou, Chuanbin; Xu, Wanying; Gong, Zhe; Fang, Wenjun; Cao, Aixin
<x xml:space="preserve">Abstract</x> Landfills stock massive amounts of minerals and materials, where soil‐like material is the primary component of stored waste in old landfills. A typical old landfill (Yingchun landfill) in China was taken as a study case. The stored wastes were sampled from different depths of the landfill, and then the soil‐like materials were screened for further analysis. Physicochemical characteristics and the fertilizer quality of the soil‐like materials were analyzed and the fertilizer effects were studied by cultivating Impatiens balsamina L. with different mixed ratios of soil‐like materials and natural soils. According to the results, soil‐like materials accounted for 75.02% of the total stored wastes and were in an advanced state of decomposition. Soil‐like materials displayed a cation exchange capacity of 84.53 cmol(+) kg−1, pH 8.14, and an electrical conductivity of 1190.55 μS cm−1, and were also characterized by high levels of organic carbon and nutrient contents compared to natural soils. The total organic carbon, total nitrogen, total phosphorus, and total potassium of soil‐like materials were 9.06, 0.16, 0.21, and 1.48%, respectively. Most of the heavy metal content was relatively lower than the law limits in China. However, As and Zn may have an environmental contamination risk. It could be shown that soil‐like materials could significantly promote growing and flowering of I. balsamina L., and were proved to be a valuable bio‐resource with utility as soil amendment, cultivating substrate, and raw materials for producing organic–inorganic compound fertilizers.